PENGEMBANGAN MEDIA PEMBELAJARAN MATERI BILANGAN BERBASIS AUDIO VISUAL MENGGUNAKAN ADOBE FLASH PROFESIONAL CS6 - RODY SATRIAWAN; FAHRURROZI FAHRURROZI; NENY ENDRIANA; NILA HAYATI; RISTU HAIBAN HIRZI; DEDY EKA HASPANI (STRATEGY : Jurnal Inovasi Strategi dan Model Pembelajaran, 2022)
This research aimed to develop audio visual based on learning media using adobe flash professional CS6 in material subject for students of seventh graders at MTs Mu'allimin NW Pancor that was valid, practical and effective. This research was a research and development (R&D) that was adapted from the ADDIE development model. There are 5 stages: (1) Analysis; (2) Design; (3) Development; (4) Implementation; and (5) Evaluation. The population was students of seventh graders , with a sample of students of VIIB . Data collection techniques used were using a questionnaire that was analyzed descriptively. The results showed that audio visual based on learning media using adobe flash professional CS6 which had been developed based on the assessment of media experts obtained by 96 with a very good category and material expert assessment was obtained by 42 with a good category. Based on students' responses to the practicality of the media it was found that the percentage of assessment was 75.35% with the practical category. Based on tests of student learning outcomes on the effectiveness of the media obtained a percentage of 88.46%. Based on the results of data acquisition shows that audio visual based learning media using adobe flash professional CS6 was feasible and can be used in the mathematics learning process of material for students of seventh graders at MTs Mu'allimin NW Pancor. ABSTRAKPenelitian ini bertujuan untuk mengembangkan media pembelajaran bilangan berbasis audio visual menggunakan adobe flash profesional CS6 untuk kelas VII MTs Mu’allimin NW Pancor yang valid, praktis, dan efektif. Penelitian ini merupakan penelitian pengembangan yang diadaptasi dari model pengembangan ADDIE. Tahapan penelitian ini ada 5 tahap, yaitu: (1) Analysis; (2) Design; (3) Development; (4) Impelementation; dan (5) Evaluation. Hasil penelitian menunjukkan bahwa media pembelajaran bilangan berbasis audio visual menggunakan adobe flash professional CS6 yang telah dikembangkan berdasarkan penilaian ahli media diperoleh sebesar 96 dengan kategori baik. Berdasarkan respon siswa terhadap kepraktisan media didapatkan persentasi penilaian sebesar 75,35% dengan kategori praktis. Berdasarkan tes hasil belajar siswa terhadap keefektifan media yang telah dikembangkan diperoleh persentase sebesar 88,46%. Berdasarkan hasil penelitian dan analisis data, dapat disimpulkan bahwa media pembelajaran bilangan berbasis audio visual menggunakan adobe flash professional CS6 layak dan dapat digunakan dalam proses pembelajaran matematika materi bilangan kelas VII MTs Mu’allimin NW Pancor.